Effect of Active Galactic Nuclei (AGN) on the Photometric and Morphologic Properties of NGC 4414 and NGC 4369 Spiral Galaxies - Hardan, Huda; Ahmed, Abdullah K (Al-Nahrain Journal of Science, 2019)
The purpose of this work is to clarify the effect of the Active Galactic Nucleus (AGN) on the properties of the galaxy. A photometric study of two galaxies by surface optical measurements techniques and by using’griz filters’ was performed. The scientific material that used in this work was obtained from ’’SLOAN DIGITAL SKY SURVEY’’ (DR7), a fuzzy color, contour maps, photometric parameters, and color indices were studied by using surface photometric technique. The work was done by Ellipse task in IRAF (Image Reduction and Analysis Facility) software from the National Optical Astronomy Observatory (NOAO).